Automatic Monitoring System Iot (Internet Of Things) Based Water Tanks - Pane, Rahmadani; Purnama, Iwan; Dar Hasibuan, Halmi; Rasyid Munthe, Ibnu (International Journal of Science, Technology & Management, 2024)
Water tanks are widely used to store water in the community. However, the filling process still uses a manual method so it cannot monitor/monitor the water level in the tank, so when the water is full in the tank until it overflows it is then turned off. Water tanks are often placed at a height to take advantage of gravity so that water can flow optimally. The high position of the water tank is difficult for users to reach to determine the quality and volume of water. The performance of this tool has 2 conditions. The first condition will discuss the water level monitoring tool in the tank. Using the tool developed, the water pump can be turned on and off automatically which is controlled using a monitoring tool using a smartphone and the Blynk application with a water level indicator. , water flow, and watervolume and Notification of water conditions via Telegram. Technology for distributing and monitoring water in tanks is still limited to conventional means by turning on and opening the water tap. For this reason, a control system is needed that can monitor and control the water volume in several tanks through one application display on a smartphone such as Telegram. By using the NodeMCU ESP8266 as a microcontroller base, an ultrasonic sensor as a water volume measuring sensor, and a Mini Water Pump, the condition of the water volume and all changes can always be monitored via notifications on Telegram. Apart from that, the tool can also be controlled automatically or manually through the commands provided on Telegram. In this way, the concept of using Telegram as a water tank volume control and monitoring system can be the right alternative choice in designing a water tank control system. The research method used is a prototyping system. The expected result is the realization of automatic floodgates to make it easier for humans to carry out their tasks and make the system run more efficiently. Apart from being automatic, this tool has the advantage that it can be controlled remotely using the internet of things. The design of this automatic sluice gate uses an Arduino Uno microcontroller as a processing tool, and is equipped with an ultrasonic sensor, water level float switch sensor, servo motor.